Perceived versus calibrated income risks in heterogeneous-agent consumption models - Tao Wang (Bank of Canada, 2023)
Models of microeconomic consumption (including those used in heterogeneous-agent macroeconomic models) typically calibrate the size of income risk to match panel data on household income dynamics. But, for several reasons, what is measured as risk from such data may not correspond to the risk perceived by the agent. This paper instead uses data from the Federal Reserve Bank of New York's Survey of Consumer Expectations to directly calibrate perceived income risks. One of several examples of the implications of heterogeneity in perceived income risks is increased wealth inequality stemming from differential precautionary saving motives. I also explore the implications of the fact that the perceived risk is lower than the calibrated level of risk either because of unobserved heterogeneity by researchers or because of overconfidence by the agents.
Keywords: D14; E21; E71; G51; 330; Monetary policy; Monetary policy and uncertainty; Business fluctuations and cycles